Profil Pasien Tuberkulosis Resistan Obat (TB RO) dengan Penyakit Paru Obstruktif Kronis (PPOK) di RSUD Dr. H. Abdul Moeloek Provinsi Lampung - Afia Farah Nabila; Tri Umiana Soleha; Chicy Widya Morfi (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Background: Drug-resistant tuberculosis (DR-TB) is an increasingly complex health issue, especially when accompanied by chronic obstructive pulmonary disease (COPD) comorbidity, which can exacerbate lung conditions, affect therapeutic response, and reduce treatment success. This study aims to describe the characteristics of DR-TB patients with COPD comorbidity at RSUD Dr. H. Abdul Moeloek from 2022 to 2024. Method: This study utilized a retrospective descriptive design. Data used were secondary data from patient medical records. Univariate analysis was performed to describe subject characteristics. Results: Among 46 patients, the majority were male (78.3%) aged 41–60 years (50%). RR-TB classification (76.1%) and long-term regimens (78.3%) dominated the findings. Therapeutic outcomes recorded 54.3% cured, 30.4% treatment completed, 8.7% failed, and 6.5% deceased. Discussion: DR-TB patients with COPD are more frequently observed in middle-aged males due to smoking exposure and occupational factors. The majority were classified as RR-TB, consistent with gradual resistance patterns. Long-term regimens were preferred as they are considered safer for lung function. Although COPD aggravates the condition, therapy remains likely to succeed with appropriate drug selection and patient adherence. Conclusion: DR-TB patients with COPD comorbidity are generally middle-aged males with a relatively good proportion of treatment success. Appropriate regimen selection and strict monitoring are required to optimize treatment outcomes.